Thermal diffusivity enhancement in nanofluids based on pyrolytic titania nanopowders: importance of aggregate morphology1. (12th June 2014) - Rondino, F.; D'Amato, R.; Terranova, G.; Borsella, E.; Falconieri, M.; Moger, Julian; Radi, Peter
<x xml:space="preserve">Abstract</x> Nanoparticle suspensions (nanofluids) have been subject of several investigations in the last few years for their potential applications, one of them being the improvement of heat transfer characteristics of thermal fluids. However, notwithstanding the numerous studies on thermal properties of nanofluids containing various kinds of nanoparticles, in many cases, the results are conflicting, and the models proposed to explain the experiments are controversial. In this paper, the thermal conductivity enhancement in dispersions, based on titania nanoparticles produced by laser‐assisted pyrolysis, is investigated using an optical technique known as forced Rayleigh light scattering. Measurements on these systems exhibited a linear relation between the thermal conductivity enhancement and the nanoparticle volume fractions with a maximum increase of 6% with respect to the base fluid ethanol at 0.6% titania content. Comparison of the experimental data with the aggregation model developed by Prasher et al. highlighted the crucial role of the morphology of pyrolytic nanoparticle aggregates on determining the thermal conductivity enhancement. Copyright © 2014 John Wiley & Sons, Ltd.